Assessing acceptability of hypertensive/diabetic patients towards mobile health based behavioral interventions in Pakistan: A pilot study. Issue 11 (November 2015) - Siddiqui, Mahrukh; Islam, Mohammad Yousuf ul; Mufti, Bushra Abid Iqbal; Khan, Natasha; Farooq, Muhammad Saad; Muhammad, Mariam Gul; Osama, Muhammad; Kherani, Danish; Kazi, Abdul Nafey; Kazi, Abdul Momin
Highlights Hypertension and Diabetes are rapidly growing chronic conditions in Pakistan with an increasing mortality rate due to poor knowledge, self-management and low quality of life. The potential positive and high scope of using Mobile Health services for management in chronic conditions like Diabetes and Hypertension in a developing country like Pakistan. The potential positive and high scope of phone call reminders against SMS reminders for self-management in Mobile Health services in Pakistan.